2021
DOI: 10.12740/pp/onlinefirst/113009
|View full text |Cite
|
Sign up to set email alerts
|

Gender dysphoria, gender incongruence and gender nonconformity in adolescence – changes and challenges in diagnosis

Abstract: Specjaliści z zakresu psychiatrii, psychoterapii i seksuologii zajmujący się leczeniem i wspieraniem pacjentów nastoletnich, w swojej praktyce mogą dostrzec znaczny wzrost zgłoszeń dotyczących nieakceptowania płci przypisanej przy urodzeniu, kwestionowania jej, odrzucania lub na różne sposoby przeżywania. Chociaż praca z osobami dorosłymi znajdującymi się w spektrum transpłciowości ma historię sięgającą lat 20-tych XX wieku, dysforia płciowa u młodzieży, zwłaszcza w ostatnich latach, jest zjawiskiem, które w s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 18 publications
1
5
0
1
Order By: Relevance
“…The boy/girl ratio in referrals to our clinic was 5.66. In a crossnatural cross-cultural comparative analysis by Cohen Kettenis symptoms (26,37,39,40). In Turkey, social intolerance for cross-gender behaviors might be greater compared to western societies where these studies on the psychological well-being of children and adolescents with GD are conducted (10).…”
Section: Discussionmentioning
confidence: 99%
“…The boy/girl ratio in referrals to our clinic was 5.66. In a crossnatural cross-cultural comparative analysis by Cohen Kettenis symptoms (26,37,39,40). In Turkey, social intolerance for cross-gender behaviors might be greater compared to western societies where these studies on the psychological well-being of children and adolescents with GD are conducted (10).…”
Section: Discussionmentioning
confidence: 99%
“…Gender dysphoria has become progressively more common and has been recognized and treated earlier over the last two decades. 27 The presentation and diagnosis of these individuals can often be a challenge due to the sensitive nature of the topic. These individuals often present in their adolescent and teenage years when their gender identity.…”
Section: Clinical Presentation and Diagnosismentioning
confidence: 99%
“…Distress may also present as signs of physical abuse from bullying such as bruises or scrapes. 27 Studies done in Germany showed that 26% of patients that presented to the clinic with gender dysphoria endorsed negative responses to their outings at school. 33 Comorbid depression and anxiety might also prompt patients to present to clinic, and further questioning is often required to reveal underlying gender dysphoria.…”
Section: Health Psychology Researchmentioning
confidence: 99%
“…The dilemmas experienced by adolescents lead to the necessity of addressing not only the nature of the reported dissatisfaction with one's biological sex, but also how this discomfort fits into the normative period of uncertainty and exploration in the young person's process of developing their psychosexuality. This is especially important since adolescents with gender dysphoria are more likely to present with co-occurring internalising disorders, such as anxiety and depression and/or externalising disorders, such as oppositional defiant disorder (Dora et al, 2021). The prevalence of autism spectrum disorders appears to be higher in these individuals compared to the general age-matched population (de Vries et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Dylematy pacjentów w wieku rozwojowym prowadzą do konieczności zmierzenia się z trudnymi pytaniami -nie tylko o naturę niezadowolenia z płci biologicznej, ale także o to, jak zgłaszany dyskomfort wpisuje się w normatywny u młodego człowieka okres niepewności i poszukiwań w procesie konstytuowania się psychoseksualności. To bardzo istotne, zwłaszcza że u osób nastoletnich z dysforią płciową dość powszechne jest współwystępowanie zaburzeń internalizacyjnych, takich jak lęk i depresja, i/lub zaburzeń eksternalizacyjnych, takich jak zaburzenia opozycyjno-buntownicze (Dora et al, 2021). Rozpowszechnienie zaburzeń ze spektrum autyzmu wydaje się w opisywanej grupie większe niż w ogólnej, analogicznej wiekowo populacji (de Vries et al, 2010).…”
Section: Introductionunclassified